In chronic spontaneous urticaria, IgE against staphylococcal enterotoxins is common and functional. Issue 7 (20th February 2018) - Altrichter, S.; Hawro, T.; Liedtke, M.; Holtappels, G.; Bachert, C.; Skov, P. S.; Maurer, M.
Abstract: Background: Chronic spontaneous urticaria (CSU) is a frequent disorder with recurrent itchy wheals and/or angioedema. Despite the known effectiveness of omalizumab therapy, the relevant IgE antigens are largely unknown. Recently, increased rates of elevated levels of IgE towards Staphylococcus aureus enterotoxins (SEs) were described in CSU. Aim: To assess the prevalence and functional relevance of IgE to SEs in CSU. Method: We investigated serum levels of IgE against SEs in 49 CSU patients and in 15 CSU patients additional specific IgE to SE components and basophil histamine release (BHR). Sera of 15 healthy controls (HCs) served as control group. Results: Twenty‐five (51%) of the CSU patients had detectable levels of SE‐IgE as compared to 5 (33%) of HCs. Specific IgE to one of the SEs, Staphylococcus enterotoxin B (SEB), was present in 5 (33%) of 15 randomly selected CSU patients vs 3 (20%) of HC. Total IgE serum levels in CSU patients were significantly correlated with SE‐IgE ( r = .52, P < .001) and SEB‐IgE ( r = .54, P = .04) serum concentrations. Interestingly, SEB‐IgE levels were strongly correlated with disease activity (UASday) in CSU patients ( r = .657, P = .01). Furthermore, BHR in response to SEB was significantly higher in basophils loaded with the serum of CSU patients compared to HC ( P < .05) and was clinically correlated with duration of disease ( r > .51, P < .05). Discussion: IgE against SEs may contribute to the pathogenesis of CSU in a subpopulation of patients. Its role and relevance in the pathophysiology of CSU need to be further analysed.